Activation of TLR7 Inhibition of Mycobacterium Tuberculosis Survival by Autophagy in RAW 264.7 Macrophages. Issue 12 (23rd May 2017) - Bao, Meng; Yi, Zhengjun; Fu, Yurong
ABSTRACT: The aim of the study was to evaluate the effect of regulation of TLR7 on Mycobacterium tuberculosis (Mtb) survival in macrophages. TLR7 expression in macrophages infected by Mtb was detected by RT‐PCR and Western blotting. Regulation of TLR7 was achieved by single strand RNA (ssRNA) or siRNA. The effects of TLR7 on Mtb survival and cell viability were detected by acid fast staining and cell counting kit‐8, respectively. Cell ultrastructure was observed via transmission electron microscopy (TEM), and autophagy related protein LC3 was analyzed by Western blotting. TLR7 in Mtb infected macrophages was up‐regulated and up‐regulation of TLR7 could eliminate intracellular Mtb. Up‐regulation of TLR7 could increase viability of Mtb infected cells, while down‐regulation of TLR7 induced decrease of cell viability compared with the controls. Autophagosome was significantly increased in the Mtb infected macrophages after up‐regulation of TLR7 and LC3‐II protein showed obvious increase compared with the controls. Autophagosome could not be detected in macrophages after down‐regulation of TLR7, rough endoplasmic reticulum was dilated, and nuclear week gap was widened. Moreover, LC3‐II protein was reduced in Mtb infected macrophages based upon the down‐regulation of TLR7. Up‐regulation of TLR7 could eliminate intracellular Mtb through autophagy. J. Cell. Biochem. 118: 4222–4229, 2017. © 2017 Wiley Periodicals, Inc. Abstract : TLR7 in Mtb infected macrophages was up‐regulated and up‐regulation of TLR7 could eliminate intracellular Mtb. Autophagosome was significantly increased in the Mtb infected macrophages after up‐regulation of TLR7 and LC3‐II protein showed obvious increase compared with the controls.